(untitled) (Research, Society and Development, 2021)
School transportation is not only a right, but a matter of citizenship. The present study aimed to identify the main irregularities that cause the paralysis of services, from the very user of this public service, to know how the means are being offered to ensure their right of access and permanence in school through the examination of the application of the monitoring instruments of school transport services in the Southern Agreste Region of the State of Pernambuco. For this, it was carried out a field research of exploratory descriptive character, which is justified and based on a literature verification composed by bibliographic and documental research and case study. The instrument applied was a questionnaire to a given population. It quantitatively measures the activities related to this variable. With this monitoring, problems were detected, whether repeated or occasional, which hurt what determines the legislation of the public policy of school transport. With the results, the following irregularity is configured: paralysis of services. Thus, it is urgently necessary to implement new elements in the management monitoring of school transportation services, from the Municipal Articulation Management (GAM/SEE) along with the Regional Education Managers.